2013
DOI: 10.1093/mnras/stt352
|View full text |Cite
|
Sign up to set email alerts
|

The SCUBA-2 Cosmology Legacy Survey: blank-field number counts of 450-μm-selected galaxies and their contribution to the cosmic infrared background

Abstract: The first deep blank-field 450µm map (1σ ≈ 1.3 mJy) from the SCUBA-2 Cosmology Legacy Survey (S2CLS), conducted with the James Clerk Maxwell Telescope (JCMT) is presented. Our map covers 140 arcmin 2 of the Cosmological Evolution Survey (COSMOS) field, in the footprint of the Hubble Space Telescope (HST) Cosmic Assembly Near-Infrared Deep Extragalactic Legacy Survey (CANDELS). Using 60 submillimetre galaxies (SMGs) detected at 3.75σ, we evaluate the number counts of 450µm-selected galaxies with flux densities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…The results of Coppin et al (2015) were based on a deep stack of SCUBA-2 (Holland et al 2013) Cosmology Legacy Survey data (Geach et al 2013) over the UKIDSS-UDS field (Lawrence et al 2007). The explanation for differences relative to the results of Coppin et al (2015) is not entirely clear.…”
Section: Irx Versus Bmentioning
confidence: 99%
“…The results of Coppin et al (2015) were based on a deep stack of SCUBA-2 (Holland et al 2013) Cosmology Legacy Survey data (Geach et al 2013) over the UKIDSS-UDS field (Lawrence et al 2007). The explanation for differences relative to the results of Coppin et al (2015) is not entirely clear.…”
Section: Irx Versus Bmentioning
confidence: 99%
“…After this stage, we used our deboosted flux densities with their associated instrumental noise levels to determine their completenesses and radial offsets. The former we computed from a spline interpolation of a two-dimensional surface of modeled flux density and instrumental noise (see Figure 4 and, e.g., Geach et al 2013), while the latter we computed from a spline interpolation of modeled S/N (see left-hand panel of Figure 5). …”
Section: Source Extractionmentioning
confidence: 99%
“…These relatively bright SMGs, which have a median redshift of z∼2.3 and SFR  100 M e yr −1 (Chapman et al 2005), have traditionally been found using bolometer cameras, such as the Submmillimetre Common-User Bolometer Array (SCUBAHolland et al 1999), mounted on single-dish telescopes, such as the 15 m James Clerk Maxwell Telescope (e.g., Coppin et al 2006;Weiß et al 2009b;Wardlow et al 2011;Casey et al 2013;Geach et al 2013). One of the main advantages of single-dish observations is that they can survey sufficiently wide areas of the sky to enable the detection of relatively large numbers of galaxies.…”
Section: Introductionmentioning
confidence: 99%